Analisis Random Walk dan Autokorelasi dalam Menguji Efisiensi Pasar Bentuk Lemah pada Indeks LQ45 - A. Mila Jamila; Nur Fadilah; Widya Wahyuni; Sri Auria Hafsa; Dirman; Suriani M (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2026)
This study aims to test weak-form market efficiency by analyzing random walk patterns and stock return autocorrelation on the LQ45 Index to find out whether historical information is still relevant for investment decisions. The data used consists of daily closing prices of stocks included in the LQ45 Index for the period January–December 2025, obtained from Yahoo Finance. Stock returns are calculated based on daily closing prices and then analyzed using the Run Test and Durbin–Watson test. The Run Test is used to check whether stock return movements are random (random walk), while the Durbin–Watson test is used to detect autocorrelation between current returns and previous period returns. The combination of these two methods is used to evaluate the characteristics of weak-form market efficiency based on randomness patterns and the relationship between returns. The research results show that stock returns on the LQ45 Index tend to move randomly and do not show significant autocorrelation. Based on the Run Test and Durbin–Watson test, it can be concluded that stock returns on the LQ45 Index reflect the characteristics of a weak-form efficient market.